Nominalization Processes in O̩ GBA (Zien Journal of Social Sciences and Humanities, 2023)
This paper examined nominalization processes in in O̩ gba, an Igboid language spoken in about forty-one communities in O̩ gba/Egbema/Ndoni Local Government Area of Rivers State, Nigeria. This study employed unstructured oral interview method of data collection. The data were analyzed using the descriptive method of morpheme-to-morpheme glossing. The study revealed that verbs in the language can be turned into nominal through morphological operations such as affixation, reduplication and compounding. The affixes that are involved in the nominalization of verbs are prefixes which is schematized as Pref. + VR, the combination of prefixes and suffixes which was schematized as ó-/ó̩ - + VR + DV where ò-/ò̩ - is a high tone harmonizing open back rounded vowel, VR is the verb root and DV is the duplicated vowel. More so, this research affirms that total reduplication alone, the combination of prefixes and reduplication. The morphological rule for the representation of these types of structure is (Pref.) + RED + VR, the rule for the derivation of gerundives is ò-/ò̩ + VR, where ò-/ò̩ is a low tone harmonizing open back rounded vowel which functions as prefix while VR is verb root. The paper also found out that the morphological operations that are productive in terms of nominalization are ò-/ò̩ + VR and Pref. + VR